Phosphatase enzyme histochemistry for studying vascular hierarchy, pathology, and endothelial cell dysfunction in retina and choroid - Lutty, Gerard A. (Vision Res, 2005)
Phosphatase enzymes cleave an inorganic phosphate from a substrate. Phosphatase enzyme histochemistry followed by flat-embedding in glycol methacrylate is extremely useful in studying retinal and choroidal vascular development and loss, since only viable blood vessels have these enzyme activities. Sites of occlusion and remodeling can be identified and analysed, resulting in new insights into the cause of occlusion. The phosphatase activities are elevated in neovascularization making possible high resolution analysis of neovascularization, the feeder vessels, and the retinal milieu in which angiogenesis occurs. Adenosine diphosphatase (ADPase) catalyzes ADP to an inorganic phosphate plus adenosine monophosphate, preventing accumulation of ADP, one of the most potent stimuli for platelet aggregation. The ADPase technique can be used in any species but this report highlights its use in dog and human retinas. The ADPase technique has yielded important insights into vaso-occlusive and vasoproliferative processes in retinopathy of prematurity, sickle cell and diabetic retinopathies. The alkaline phosphatase flatembedding technique is useful in evaluating dog, cat, and human choroidal vasculatures. It has permitted quantification of the loss of choriocapillaris in diabetic choroidopathy and of the RPE and choriocapillaris in geographic atrophy and exudative age-related macular degeneration.